The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fpubh.2022.876105
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices Associated With Diabetic Foot Prevention Among Rural Adults With Diabetes in North China

Abstract: BackgroundThe diabetic foot is a global threat to public health because it can result in infection and amputation, as well as cause the patient to experience considerable pain and incur financial costs. The condition of patients with diabetic foot in North China is distinguished by more severe local ulcers, a worse prognosis, and a longer duration of disease than that of patients with diabetic foot in the south. Through appropriate preventive measures, the diabetic foot can be effectively avoided. This study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The strategy of community engagement has emerged as a highly effective and impactful approach for advancing knowledge, fostering positive attitudes, and encouraging beneficial practices among patients living with diabetes. By actively involving patients in their personalized treatment plans, there is a notable and significant improvement in their adherence to medical recommendations and overall satisfaction with their healthcare experience [ 19 ]. This collaborative and patient-centered approach not only empowers individuals to take ownership of their health but also improves the overall effectiveness of diabetes management, ultimately leading to improved health outcomes and a better quality of life for those affected by this condition [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The strategy of community engagement has emerged as a highly effective and impactful approach for advancing knowledge, fostering positive attitudes, and encouraging beneficial practices among patients living with diabetes. By actively involving patients in their personalized treatment plans, there is a notable and significant improvement in their adherence to medical recommendations and overall satisfaction with their healthcare experience [ 19 ]. This collaborative and patient-centered approach not only empowers individuals to take ownership of their health but also improves the overall effectiveness of diabetes management, ultimately leading to improved health outcomes and a better quality of life for those affected by this condition [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that there were more confounding factors in patients with PAD, such as more complications, interventions, and utilization of drugs related to hyperlipidemia, hypertension, and antiplatelet, which would attenuate the relationship between TyG and severity of DFUs in PAD subgroup. The current studies suggested that diabetic foot and amputation prevention strategies should focus on men, working freelancers and those with long‐term diabetes [37–39]. Increasing knowledge with regard to diabetic foot would help avoid further complications and reduce the occurrence of DFUs.…”
Section: Discussionmentioning
confidence: 99%
“…Awareness of the susceptibility of diabetic feet and active measures to prevent it are separate entities. A possible explanation is that diabetic feet develop slowly over time, which leads them to not realize the gravity of complications [ 22 ]. As for practices, 93.5% wash their feet daily, consistent with other studies, with over 80% doing so [ 11 ].…”
Section: Discussionmentioning
confidence: 99%